2013
DOI: 10.1021/ja411060p
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Photophysics of the Spinach–DFHBI RNA Aptamer–Fluorogen Complex To Improve Live-Cell RNA Imaging

Abstract: The use of aptamer-fluorogen complexes is an emerging strategy for RNA imaging. Despite promise for cellular imaging and sensing, the low fluorescence intensity of the Spinach-DFHBI RNA aptamer-fluorogen complex hampers its utility in quantitative live-cell and high-resolution imaging applications. Here we report that illumination of the Spinach-fluorogen complex induces photoconversion and subsequently fluorogen dissociation, leading to fast fluorescence decay and fluorogen concentration-dependent recovery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 45 publications
(81 reference statements)
7
148
1
Order By: Relevance
“…3). Therefore, DFHBI and its associated ions and waters can more readily exchange with bulk solvent, consistent with the photophysical properties of Spinach 6,26,27 .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…3). Therefore, DFHBI and its associated ions and waters can more readily exchange with bulk solvent, consistent with the photophysical properties of Spinach 6,26,27 .…”
Section: Resultssupporting
confidence: 66%
“…The two K + ions are separated by 3.8 Å, as previously seen in other G-quadruplexes 24,25 . The complex topology required for the Spinach G-quadruplex to connect to flanking duplexes on both sides may explain the folding difficulties exhibited by some Spinach sequences 8,26,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Moreover, we observed that crystals melted and cracked during the experiment, suggesting conformational changes consistent with a DFHBI photo-inactivation model in which the dye isomerizes upon illumination and is rapidly ejected from the aptamer (Han et al 2013). Altogether, these results suggest that the crystallized form of the complex is representative of its native state in solution.…”
Section: Molecular Engineering and Crystallogenesissupporting
confidence: 67%
“…Continuous bathing also requires little to no background fluorescence for standard wide-field imaging techniques. Rapid excitation of the fluorescent complexes can result in isomerization, photoinduced unbinding of the fluorogenic probe and diminished signals, although fluorophore recycling is a useful property for minimizing photobleaching 72 . Lastly, lower dissociation constants ( K D ) will need to be demonstrated for low-copy RNA detection, and fluorophores with improved photophysics should enable truly single-molecule imaging.…”
Section: Methods For Labeling Of Rnamentioning
confidence: 99%